Positioning Of Rajah Court Hotel To Gain A Competitive Edge / Harris Tidan - Tidan, Harris (University Technology MARA, 2001)
This research is aim to study the positioning ofRajah Court Hotel in order to gain a competitive edge. Being purely for academic purposes, the study hope to understand the complex set of perceptions, impressions and feelings of Rajah Court Hotel guest or potential guest compared to its competitors. Survey was done, where data and information were collected via primary and secondary data. For the purpose ofthis study RCH guest and Tour and Travel Agency within Kuching City were taken in as the sampling through cluster sampling method. From the study it was found out that RCH positioning as “a value Hotel” is an attractive strategy. The study also found that there was some inconsistency between the marketing communication message used to promote RCH and the positioning ofRCH. Therefor, recommendations was presented as to amend the inconsistency occurs in order for RCH to fulfill the basic rule ofbusiness by writing a sen one ofnet profit after depreciation.